New approaches to the distribution activities of LLC Belarus Tractor (Budapest) as a distribution network company - A.G. Shumilin; V.V. Mojder (Економіка, управління та адміністрування)
The article discusses the distribution activities of LLC Belarus Tractor in the European market in the context of general exports. The Hungarian tractor market, farmers’ requests, competitors’ positions, the most effective methods of selling agricultural machinery are analyzed. The dynamics of the sale of tractors «Belarus» in comparison with other manufacturers and the results achieved are analyzed. Such forms of Belarus Tractor commercial work as event marketing, Internet marketing, advertising, participation in plowing competitions, etc. are proposed.